Molecular characterization of nosA, a Pseudomonas stutzeri gene encoding an outer membrane protein required to make copper-containing N2O reductase. - Lee, H S (1991)
A Pseudomonas stutzeri gene (nosA) encoding an outer membrane protein was cloned into the broad-host-range vector pRK290 and expressed in a mutant lacking the protein. Deletion analysis identified the approximate extent of the nosA region which was sequenced, and it was found to contain an open reading frame encoding 683 amino acids including a presumed signal sequence of 44 amino acids. The putative processed form had a molecular weight of 70,218, characteristics typical of outer membrane proteins, and considerable amino acid sequence homology with Escherichia coli BtuB. A short stretch of amino acids was homologous with the E. coli TonB-dependent outer membrane proteins, BtuB, IutA, FepA, and FhuA, suggesting a homologous function: interaction with a periplasmic protein or uptake of a specific substrate.